BLOGGING AS A MODERN FORM OF POLITICAL COMMUNICATION - M. M. Abazalieva; A. K. Botasheva (Современная наука и инновации)
The article is devoted to the study of blogging as a modern form of political communication. The relevance of such studies is due to the weak development of the problems of influence on the socio-political situation of opinion leaders - bloggers who are able to actively interfere in the formation of the political agenda, acting as a mechanism for consolidating and mobilizing citizens. A number of provisions and conclusions are formulated, indicating that 1) blogging has objectively become a means of broadcasting socially significant meanings; 2) political discourse will increasingly depend on the purposeful generation of certain information by public opinion leaders.